(untitled) (Journal of Bhuwanishankar, 2023)
This study explores the students’ experiences on English as a medium of instruction in education. This qualitative research used narrative inquiry as a research approach. The semi-structured interview was used as a data collection process and interview guidelines including open-ended questionnaires were used as research tools. The data were collected from the purposively selected two participants who were studying at bachelor level. This study revealed that the students account for the English medium of instruction as a supportive policy for them to be sold out in the global market; nevertheless, they experience their anxieties about this practice in and outside the educational setting.